2007
DOI: 10.1080/17429140701422512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varied water regimes on root length, dry matter partitioning and endogenous plant growth regulators in sunflower (Helianthus annuusL.)

Abstract: A field experiment was conducted to quantify the effect of varied water regimes on root length, partitioning of dry matter and plant growth regulators by using sunflower genotypes differing in maturity and drought tolerance. Significant depressing effect of drought stress was evident on traits (i.e., reproductive dry matter, leaf area index and cytokinin concentrations in leaves). However, root/shoot, reproductive/vegetative ratios and Abscisic acid (ABA) concentration were found to increase under drought stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…The result indicated that drought stress stimulates roots to lengthen and increased root number, to adapt against the stress. A similar result is reported by literature [23] root length were increased during the drought stress compared to a well-watered plant.…”
Section: Changes In Maize Growth Under Drought Stresssupporting
confidence: 91%
“…The result indicated that drought stress stimulates roots to lengthen and increased root number, to adapt against the stress. A similar result is reported by literature [23] root length were increased during the drought stress compared to a well-watered plant.…”
Section: Changes In Maize Growth Under Drought Stresssupporting
confidence: 91%
“…5). In this regard, there have been reports on its accumulation in stressed plants (De Diego et al, 2013) and on the involvement of defense responses during plant adaptation to drought (Rauf and Sadaqat, 2007). This may be directly related to RWC, as in September 2015, there was significant difference between treatments, with a decrease compared to T100 of around 17% for non-irrigated treatment (Fig.…”
Section: Plant Hormone Responses To Deficit Irrigation Strategies In mentioning
confidence: 86%
“…These results may be due to the lowest irrigation water level diminished plant water contents of sunflower, then leaf water potential, biomass, cell enlargement and growth with closing stomata due to mainly turgor loss [32] [33]. Consequently, the lowest irrigation water level resulted in lessening leaf growth and decreasing relative dry matter portioning into the root and shoot/root ratio [34] which reflected negatively on head seed weight. Sunflower plants that suffered from water deficit in the root zone have small root system and weak shoot growth and this in turn reduce both the vegetative growth and the yield [35].…”
Section: Discussionmentioning
confidence: 99%